Effective food system innovations: An evidence map - Lecoutere, Els; Berg, Marrit van den; de Brauw, Alan (International Food Policy Research Institute, 2021)
This interactive evidence map presents an inventory of evidence of the effects of different types of food system innovations targeting the food environment and consumers on diets and nutrition related outcomes along the pathways of change in the food environment and among consumers. The inventory includes 150 studies with evidence primarily for Bangladesh, Ethiopia, Nigeria, and Vietnam. These countries represent a population of over 600 million people and a range of diet and (sub)-national food system contexts at various stages of food system transformation and urbanization.